‘Radicalisation of Laïcité’: What’s in a Word? - Quivooij, Romain (2018)
Misleading interpretations of laïcité, France’s way to implement secularism, have long been threatening the country’s social cohesion. What explains the longevity of these approaches, how do their various proponents justify them and why should they be labelled “radical”?